Transformative Teaching: An Examination Of Relational Pedagogy In The Film 'To Sir, With Love' Directed By James Clavell And Its Impact On Students’ Attitudes And Behaviours - Félix Fernandes Coutinho; Sidonio Antonio Pires (Jurnal Pendidikan Indonesia, 2024)
This research, titled “Transformative Teaching: An Examination of Relational Pedagogy in the Film ‘To Sir, with Love’,” explores the impact of Mr. Thackeray’s relational pedagogy on students' attitudes and behaviors. The study addresses two key questions: 1) How are the key elements of relational pedagogy—care, attentive presence, interpersonal communication, and trust—portrayed in the film? 2) How do these elements impact students’ behaviors and attitudes, particularly for Pamela, Potter, and Denham? Using a qualitative approach, the research employs document analysis and thematic analysis. The findings reveal that Mr. Thackeray effectively implemented the four key elements of relational pedagogy, resulting in positive changes even among disengaged and resistant students. His approach fostered greater commitment, politeness, enthusiasm, and cooperation, as well as deepened his understanding of students’ perspectives. By integrating students' viewpoints into classroom discussions, Thackeray empowered them to freely express themselves without fear of marginalization. These pedagogical strategies led to notable transformations in students' behaviors and attitudes, particularly for Pamela, Potter, and Denham. In conclusion, the research highlights the effectiveness of relational pedagogy in promoting positive change in student behavior and attitudes, emphasizing care, attentive presence, communication, and trust as essential components for transformative teaching.